Efficacy of novel recombinant fowlpox vaccine against recent Mexican H7N3 highly pathogenic avian influenza virus. Issue 16 (10th April 2019) - Criado, Miria Ferreira; Bertran, Kateri; Lee, Dong-Hun; Killmaster, Lindsay; Stephens, Christopher B.; Spackman, Erica; Sa e Silva, Mariana; Atkins, Emily; Mebatsion, Teshome; Widener, Justin; Pritchard, Nikki; King, Hallie; et al.
Highlights: rFPV-H7/3002 vaccine protected chickens against challenge Mexican 2015 H7N3 HPAIV. rFPV-H7/2155 vaccine protects against the 2012 outbreak virus but not 2015 H7N3 HPAIV. 2015 Mexican H7N3 HPAIV have gained additional N-glycosylation sites on the HA. The importance of updating vaccines for long-term effective control of H7 HPAIV. Abstract: Since 2012, H7N3 highly pathogenic avian influenza (HPAI) has produced negative economic and animal welfare impacts on poultry in central Mexico. In the present study, chickens were vaccinated with two different recombinant fowlpox virus vaccines (rFPV-H7/3002 with 2015 H7 hemagglutinin [HA] gene insert, and rFPV-H7/2155 with 2002 H7 HA gene insert), and were then challenged three weeks later with H7N3 HPAI virus (A/chicken/Jalisco/CPA-37905/2015). The rFPV-H7/3002 vaccine conferred 100% protection against mortality and morbidity, and significantly reduced virus shed titers from the respiratory and gastrointestinal tracts. In contrast, 100% of sham and rFPV-H7/2155 vaccinated birds shed virus at higher titers and died within 4 days. Pre- (15/20) and post- (20/20) challenge serum of birds vaccinated with rFPV-H7/3002 had antibodies detectable by hemagglutination inhibition (HI) assay using challenge virus antigen. However, only a few birds (3/20) in the rFPV-H7/2155 vaccinated group had antibodies that reacted against the challenge strain but all birds had antibodies that reacted against the homologous vaccine antigen (A/turkey/Virginia/SEP-66/2002) (20/20). One possible explanation for differences in vaccines efficacy is the antigenic drift between circulating viruses and vaccines. Molecular analysis demonstrated that the Mexican H7N3 strains have continued to rapidly evolve since 2012. In addition, we identified in silico three potential new N-glycosylation sites on the globular head of the H7 HA of A/chicken/Jalisco/CPA-37905/2015 challenge virus, which were absent in 2012 H7N3 outbreak virus. Our results suggested that mutations in the HA antigenic sites including increased glycosylation sites, accumulated in the new circulating Mexican H7 HPAIV strains, altered the recognition of neutralizing antibodies from the older vaccine strain rFPV-H7/2155. Therefore, the protective efficacy of novel rFPV-H7/3002 against recent outbreak Mexican H7N3 HPAIV confirms the importance of frequent updating of vaccines seed strains for long-term effective control of H7 HPAI virus.